Material Flow Analysis as a Decision Supporting tool for Faecal Sludge Resource Recovery: Mathematical formulation and quantification - Mkude, Isabela T.; Mbwette, Tolly; Kimwaga, Richard; Gabrielsson, Sara (Tanzania Journal of Engineering and Technology, 2019)
In this work, a conceptual framework for faecal sludge (FS) management and resource recovery in Dar es Salaam city was developed. Material Flow Analysis (MFA) approach was used to assess and quantify the current materials and nutrients to support on decisions for nutrient recovery and minimize environmental pollution in three unplanned settlements of Manzese, Keko and Kipawa in Dar es Salaam city. Nitrogen and Phosphorus were chosen as indicators for the evaluation of the process. The results showed that about 75% of the Dar es Salaam city population relies on pit latrines and 15% connected to septic tanks, translating to a large amount of faecal sludge being contained onsite. The situational analysis study on faecal sludge management (FSM) showed that the collection, treatment and proper disposal of FS are the major challenges that pose risks to public health. Currently, 57% of faecal sludge generated in Dar es Salaam is disposed to the environment inappropriately. Onsite Sanitation Systems in all study areas are the main polluters, discharging large quantity of nutrients to the environment. About 37.7% of faecal sludge is with large amount of nutrients emptied from onsite sanitation systems discharged to the environment and through seepage to the groundwater. Keywords: Faecal sludge; Material flow analysis; Resource recovery; unplanned settlements.